Design Discourse in Discount Shopping Context: Textual Analysis With Critical Studies Perspective and Deconstructionist Theory - Talu, Nilüfer; Talu, Nilüfer (Intellect Ltd., 2024)
In consumption culture, individuals need things to update their selves or to repre-sent their identities. The more they update their belongings, the more they feel unsatisfied. In this cultural recycling, everyday objects become objects of desire, while the notion of design functions to create attraction. The problem originates in the disengagement of subjects–objects in which the capitalist economic system gets benefits sustaining the cycle of mass production-consumption. To get more benefit, this cycle is sped up along with discount shopping context. The study aims to produce a design discourse in discount shopping context in relevance of the issues of individuality and ethics. The method is a textual analysis with critical studies perspective and deconstructionist approach. The texts are the questionnaire transcripts written by fifteen women. Critical studies perspective clarifies power relations between capitalist economic system and consumer; and deconstructivist approach determines binary relations in relevance of individuality, and ethics and heterogeneity of the texts concerning to design. Along with these two approaches, textual analysis creates a discursive structure. The structure is used to generate a design discourse in which the meaning of design is situated. In this structure, design would be something in a specific heterogeneity and relations around the matters of individuality and ethics. The discursive structure is of importance that summarizes the method used and determines all coherencies around the definitions of design. This structure also could be a useful source for the production of other critical discourses on the relations of subjects–objects and the position of design in consumption culture. © 2023 Intellect Ltd Article.
Keywords: Consumption culture; Cultural recycling; Design discourse; Discount shopping; Ethics; Individuality